An Augmentation in a Readymade Simulators Used for MANET Routing Protocols: Comparison and Analysis - Pandey, Neeraj Kumar; Mishra, Amit Kumar (International Journal of Computer Sciences and Engineering, 2014)
A Mobile ad-hoc Network (MANET) is a collection of self oriented mobile nodes dynamically organize a temporary network without any fixed infrastructure and centralized administration control stations wirelessly. In this paper we discuss various readymade simulators and their disadvantages over simulation methodology. Here we are introducing a new simulator and its advantage over traditional one. The various routing protocols are widely analyzed and compared using various simulating environment. The proposed work is basically emphasized on the augmentation in the NS-2 and the Qualnet for standard simulation.